Harnessing Streptomyces for the Management of Clubroot Disease of Chinese Cabbage (Brassica rapa subsp. Pekinensis) - Shan Chen; Yang Zheng; Qing Wang; Rong Mu; Xianchao Sun; Guanhua Ma; Liezhao Liu; Jiequn Ren; Kuo Huang; Guokang Chen (Plants)
Clubroot, caused by Plasmodiophora brassicae Woronin, poses a major threat to Chinese cabbage (Brassica rapa subsp. pekinensis) production worldwide, significantly impacting crop yield, quality, and economic value. Biological control represents a promising approach since it is non-toxic and eco-friendly, and it reduces the risk of pathogen resistance development. In this study, our objective was to screen for actinomycetes that can effectively inhibit clubroot. We screened 13 actinomycete strains, identifying 2, XDS3-6 and CD1-1, with substantial in vivo inhibitory effects, achieving infection suppression rates above 64% against P. brassicae. Phylogenetic analysis classified XDS3-6 and CD1-1 as Streptomyces virginiae and Streptomyces cinnamonensis, respectively. Both strains exhibited protease and glucanase production capabilities, essential for pathogenic suppression. Additionally, these strains induced host defense responses, as evidenced by increased jasmonic acid (JA) and salicylic acid (SA) accumulation and elevated activities of defense-related enzymes. Colonization studies of XDS3-6 and CD1-1 mutant strains in cabbage roots indicated sustained root colonization, with peak colony-forming units (CFUs) at 20 days post-inoculation, reaching 11.0 × 104 CFU/g and 8.5 × 104 CFU/g, respectively, and persisting for at least 30 days. Overall, these findings underscore the potential of Streptomyces strains XDS3-6 and CD1-1 as effective biocontrol agents, providing a theoretical foundation for their application in managing clubroot in Chinese cabbage.